Artemis Fowl - Colfer, Eoin. (New York Hyperion Books For Children, 2001)
When a twelve-year-old evil genius tries to restore his family fortune by capturing a fairy and demanding a ransom in gold, the fairies fight back with magic, technology, and a particularly nasty troll.
"Talk Miramax Books."
Keywords: Fairies -- Fiction; Kidnapping -- Fiction; Magic -- Fiction; Mothers and sons -- Fiction; England -- Fiction